The Impact of Metacognitive Capabilities on Product and Process Innovations in Supply Chain Relationships - Young Sik Cho; Kevin W. Linderman (IEEE Access)
This study explores how organizations can capture and create knowledge in supply chain relationships. In particular, this study investigated the impact of metacognitive capabilities on knowledge creation in supply chain networks. The research model was empirically verified using sample data from 151 U.S. corporations. Empirical evidence showed that organizations with strong metacognitive capabilities tend to more effectively externalize tacit knowledge gained from supply chain activities into explicit knowledge outcomes such as product and process innovations. These results suggest that organizations can better handle the complex challenges of product and process innovation when leveraging metacognitive capabilities. The practical and theoretical implications of the findings and future research agendas are discussed in depth.